Promising Role of ANGPTL4 Gene in Diabetic Wound Healing. (March 2014) - Arya, Awadhesh K.; Tripathi, Kamlakar; Das, Parimal
Diabetes mellitus (DM) is one of the severe metabolic disorders of carbohydrate metabolism worldwide. Developing countries are at higher risk of DM, and there is significant evidence that it is epidemic in many economically developing and newly industrialized countries. Among all other complications associated with DM, delayed wound healing is a major concern in diabetic patients. Wound healing is a natural healing process that starts immediately after injury. This involves interaction of a complex cascade of cellular events that generates resurfacing, reconstitution, and restoration of the tensile strength of injured skin. There are multiple factors responsible for delayed wound healing among which the contribution of DM has been well documented. The wound healing process is also delayed by the metabolic, vascular, neurological, and inflammatory alterations, which are well known in both type 1 and type 2 diabetes. Keratinocytes are crucial for wound re-epithelialization, and defects in directed migration of keratinocytes due to DM are associated with the delayed wound healing process. Many factors responsible for re-epithelialization have been identified, characterized, and well described; however, the genes responsible for the healing process have only partially been illustrated. This article will therefore focus on the efficacy of ANGPTL4 (angiopoietin-like 4) gene, which plays a novel role in keratinocyte migration during wound healing.